Alcalase-hydrolyzed oyster (Crassostrea rivularis) meat enhances antioxidant and aphrodisiac activities in normal male mice. (June 2019) - Zhang, Ziran; Su, Guowan; Zhou, Feibai; Lin, Lianzhu; Liu, Xiaoling; Zhao, Mouming
Abstract: The antioxidant and aphrodisiac properties of oyster meat (OM) and its hydrolysates by alcalase (OMA) were compared. The results showed that OMA displayed a higher antioxidant activity than OM with or without gastrointestinal digestion. Furthermore, the study reported that oral administration of OM or OMA could induce aphrodisiac activities and consequently enhance the sexual behavior in normal male mice, at a dose of 250 mg/kg. Additionally, OMA also exhibited better antioxidant activity in vivo than OM by improving the activities of the endogenous cellular antioxidant enzymes and decreasing the MDA levels, which may be helpful in improving the sexual function. These results indicated that oysters' could be a potential functional ingredient with antioxidant and aphrodisiac activities, and the activities could be improved by alcalase hydrolysis. Graphical abstract: Unlabelled Image Highlights: OMA displayed higher antioxidant activity both in vitro and in vivo . OMA could improve the sexual function of normal male mice more efficiently. The antioxidant activity may contribute to the aphrodisiac property.